DESAIN ALAT HITUNG KECEPATAN SUDUT BERBASIS SENSOR MAGNETIK FLUXGATE - Yulkifli, Yulkifli; Anwar, Zul; Djamal, Mitra (Sainstek : Jurnal Sains dan Teknologi, 2010)
This paper explains the design of angular velocity apparatus (Gyrometer) base on fluxgate sensor. The design of sensor elements consists of the double secondary coil (pick-up) and excitation coil with 10 layers, core layer is put into the isolative cavity. Fluxgate magnetic sensor works based on the principles of second harmonics, the intensity of magnetic fields proportional to the output sensor voltage. Based on data analysis on to sensor characterization it was obtained that the sensitivity 4.52 mV/?T, ±20 ?T in ranges.  The maximum absolute error obtained from polynomial function approach in 0.53 ?T and the relative error is 1.3% on magnetic fields ~19 ?T. In this research the sensor can measure the frequency in the maximum absolute and relative  error 0.68, 0.58, 0.17, 0.71 and 0.026%, 0.022%, 0.006%, 0.021%, whereas the disc magnet with the number of magnet 2, 4, 8 and 16 respectively.Key words: angular velocity, fluxgate sensor, coil, second harmonic